This study was to analyze factors influencing the performance of agricultural extension workers and their impact on the competence of cacao farmers. A number of 116 agricultural extension workers, 116 groups of farmer leaders and 232 cacao farmers from four districts in South Sulawesi were participated in this study. LISREL program with SEM was used in analyzing data. The result shows that the agricultural extension workers performance was influenced significantly by characteristic, competence, - Sapar .; Amri Jahi; Pang S. Asngari; Amiruddin Saleh; I G. Putu Purnaba (Forum Pasca Sarjana, 2011)
This study was to analyze factors influencing the performance of agricultural extension workers and their impact on the competence of cacao farmers. A number of 116 agricultural extension workers, 116 groups of farmer leaders and 232 cacao farmers from four districts in South Sulawesi were participated in this study. LISREL program with SEM was used in analyzing data. The result shows that the agricultural extension workers performance was influenced significantly by characteristic, competence, motivation and self reliance. The total impact of them was 71%. The suggestion was that their performance must be improved by providing special training to improve their capability in agricultural extension planning, monitoring and evaluation, agricultural extension development and technology dissemination. Key words: agricultural extension workers, competence of cacao farmers, performance